Catastrophes and Weddings. Chachi Ritual as Metamorphosis - Istvan Praet (Journal de la Société des Américanistes)
Catastrophes and Weddings. Chachi Ritual as Metamorphosis. A question that has intrigued anthropologists for a long time is why catastrophic anxieties are so omnipresent among Amerindian peoples. Known in the literature as « millenarianism », fears of an apocalypse appear time and again, both in lowland and highland South America. This article aims to contribute to a better understanding of this phenomenon by examining notions of metamorphosis or « shape-shifting ». The particular case described examines the link between catastrophes and the wedding festival of the Chachi, Amerindians from the Pacific coast of Ecuador.